Effects of connectedness to nature on moral licensing. - Chang, Wei Ling. (2011)
Research showed that performing green behaviours can lead to a subsequent bad deed if the opportunity arises. This is termed the moral licensing effect. In this study, connectedness to nature is predicted to moderate this effect. 80 participants were given seven natural or artificial objects to touch and rate to manipulate their level of connectedness to nature. Whether they perform a good or a bad deed was also manipulated by reusing or marketing two objects. Moral licensing was measured by the amount of chocolates taken by the participants at the end of the experiment. Results revealed that connected participants took more chocolates after a good deed but less after a bad deed than unconnected participants (p = 0.03). However, the differences were not significant (p > 0.05). This result could affect how governmental agencies tailor their green campaigns and policies